Evaluation of East African bananas for resistance to Fusarium Oxysporum f. Sp. cubense race 1 - Ndayihanzamaso, Privat (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDAgric)--Stellenbosch University, 2020.